2021
DOI: 10.3389/fcimb.2021.761417
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Determinants and Plasmid-Mediated Colistin Resistance mcr Genes in Gram-Negative Bacteria Isolated From Bovine Milk

Abstract: A major increase of bacterial resistance to colistin, a last-resort treatment for severe infections, was observed globally. Using colistin in livestock rearing is believed to be the ground of mobilized colistin resistance (mcr) gene circulation and is of crucial concern to public health. This study aimed to determine the frequency and virulence characteristics of colistin-resistant Gram-negative bacteria from the milk of mastitic cows and raw unpasteurized milk in Egypt. One hundred and seventeen strains belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…Since the first colistin-resistant mutant that was reported in 1981 ( Vaara et al, 1981 ), colistin resistance has been evolving in several microorganisms like A. baumannii ( Potron et al, 2019 ), K. pneumoniae ( Shankar et al, 2019 ; Tartor et al, 2021b ), and E. cloacae ( Huang et al, 2019 ). A recent study has reported mcr -harboring isolates from animals and humans ( Luo et al, 2020 ) and another group has isolated mcr -positive E. coli and K. pneumoniae from cancerous patients in Egypt ( Zafer et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first colistin-resistant mutant that was reported in 1981 ( Vaara et al, 1981 ), colistin resistance has been evolving in several microorganisms like A. baumannii ( Potron et al, 2019 ), K. pneumoniae ( Shankar et al, 2019 ; Tartor et al, 2021b ), and E. cloacae ( Huang et al, 2019 ). A recent study has reported mcr -harboring isolates from animals and humans ( Luo et al, 2020 ) and another group has isolated mcr -positive E. coli and K. pneumoniae from cancerous patients in Egypt ( Zafer et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the low incidence of the mcr gene in Pseudomonas compared to other microorganisms in ESKAPE pathogens, this raises the question of the fitness barrier or transferability properties of the mcr gene among Pseudomonas. The transmissibility of mcr genes in P. aeruginosa was demonstrated by Tartor et al via conjugation with E. coli J53 (Tartor et al, 2021). Four mcr genes, mcr-1, mcr-2, mcr-3, and mcr-7, were able to transfer into the recipient bacteria and increased the MIC of the recipient cells up to 64 mg/ml (Tartor et al, 2021).…”
Section: The Epidemiology Of the Mcr Gene Inmentioning
confidence: 98%
“…Ahmed et al collected fecal samples from migratory birds in Egypt during the winter season and detected MCR-1 in P. aeruginosa (Ahmed et al, 2019). Some studies have detected mcr genes in cow's milk, animal meat, and soil (Fujihara et al, 2015;Javed et al, 2020;Tartor et al, 2021). It is noteworthy that the oldest specimen was retrieved from the environment in 1983 but was never recognized until the WGS era (Fujihara et al, 2015).…”
Section: The Epidemiology Of the Mcr Gene Inmentioning
confidence: 99%
“…The mcr genes encode phosphoethanolamine transferases enzymes which change the lipid A portion of the lipopolysaccharides (LPS), suppressing colistin binding ( 9 ). The mcr genes have been reported not only from various livestock origins (pigs, poultry, bovine) ( 10 , 11 ) and food products ( 12 ) but also from the environment as well as from humans ( 13 ). Since the extensive usage of colistin in livestock farms played a major role in the occurrence of colistin resistant mcr genes, controlling the dissemination of these resistant genes from farms to the environment has become a critical concern ( 14 ).…”
Section: Introductionmentioning
confidence: 99%